Complement in paroxysmal nocturnal hemoglobinuria: exploiting our current knowledge to improve the treatment landscape - Mastellos, Dimitrios C (Expert Rev Hematol, 2014)
Paroxysmal nocturnal hemoglobinuria (PNH) is a rare hematological disorder associated with an acquired deficiency in glycophosphatidylinositol-anchor biosynthesis that renders erythrocytes susceptible to complement attack. Intravascular hemolysis via the membrane attack complex is a clinical hallmark of the disease, and C5 blockade is currently the only approved treatment for PNH. However, residual anemia is an emerging observation for many PNH patients receiving anti-C5 treatment. A range of complement-targeted therapeutic approaches, encompassing surface-directed inhibition of C3 convertases, blockade of membrane attack complex assembly or C3 interception using peptidic inhibitors, has yielded promising results and offers leverage for even more effective treatment of PNH. This article discusses recent advances in this rapidly evolving field, integrating critical perspectives from preclinical PNH models and diverse complement modulation strategies with genetic insights and therapy response profiles. It also evaluates the relative efficacy, limitations and benefits afforded by C3 or C5 inhibition in the context of PNH therapeutics.